Homemade concentrate preparation for fattening sheep - Aberra, Adie; Getahun, Elizabeth; Bezabih, Melkamu; Worku, Tigist (International Livestock Research Institute, 2024)
For a sheep fattening business to be profitable, the sheep must attain a marketable weight within 70–90 days. A fattening ration that contains ingredients rich in carbohydrates, protein and minerals is key to this. Farmers who fatten sheep in Basona Werena and the neighbouring weredas (districts) prepare homemade rations to replace factory by-product feeds.